2019
DOI: 10.1177/1094428119840801
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Construct Validity of a Team Processes Survey Measure

Abstract: Marks, Mathieu, and Zaccaro (2001) advanced a theory and framework of team processes that has garnered much attention and guided numerous investigations. They proposed that 10 first-order constructs (e.g., strategy formulation, coordination, conflict management) would map to three second-order constructs (i.e., transition, action, and interpersonal). Despite the popularity of this framework, we are unaware of any validated multiitem measures of the team processes they identified. Accordingly, we develop and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 75 publications
3
72
0
1
Order By: Relevance
“…The observation measure provides a way to capture a team level measure of psychological safety that also includes staff members who do not complete the survey. In addition, the observation measure addresses calls for new methods of measurement that can complement survey measures and provide further insights into team dynamics, while minimising intrusiveness [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation measure provides a way to capture a team level measure of psychological safety that also includes staff members who do not complete the survey. In addition, the observation measure addresses calls for new methods of measurement that can complement survey measures and provide further insights into team dynamics, while minimising intrusiveness [17].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to have worsened recently as the ongoing covid-19 pandemic has increased both physical and mental exhaustion among healthcare professionals [15,16]. A recent paper by Mathieu and colleagues [17] calls for new methods of measurement which can complement surveys by providing additional insights into team dynamics. The observation measure presented as part of this paper addresses this need and allows for repeated tracking of healthcare team dynamics without requiring their time.…”
Section: Introductionmentioning
confidence: 99%
“…Other emergent states may need to be included in TLC. One avenue for future research in that direction is to validate TLC as a second-order construct, similar to what Mathieu et al (in press) have done with the action, transition, and interpersonal processes of teamwork proposed by Marks et al (2001). Researchers need to map the many emergent states that have proliferated throughout the past decades or so, put them under larger umbrellas (second-order constructs), and test them empirically.…”
Section: Discussionmentioning
confidence: 99%
“…For example, meta-analytic research has found that virtual teams tend to communicate less and engage less in knowledge sharing behaviors (Mesmer-Magnus & DeChurch, 2009;Ortiz de Guinea et al, 2012). Mathieu et al (2019) also reported that virtual teams engaged less in transition (i.e., planning activities), action, and interpersonal processes than nonvirtual teams. Overall, this research suggests that high levels of virtuality make it harder for teams to engage in interdependent activities and smooth coordination.…”
Section: Team Processes and Their Role In Virtual Team Functioning And Performancementioning
confidence: 99%